2015
DOI: 10.1016/j.jaac.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Therapeutic Horseback Riding in Children and Adolescents With Autism Spectrum Disorder

Abstract: Objective This study expands previous equine-assisted intervention research by evaluating the effectiveness of therapeutic horseback riding (THR) on self-regulation, socialization, communication, adaptive, and motor behaviors in children with autism spectrum disorder (ASD). Method Participants with ASD (ages 6–16 years; N=127) were stratified by nonverbal IQ standard scores (≤ 85 or > 85) and randomized to one of two groups for 10 weeks: THR intervention or a barn activity (BA) control group without horses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
277
1
32

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 192 publications
(329 citation statements)
references
References 34 publications
19
277
1
32
Order By: Relevance
“…After independently rating each article using the AACPDM rating scale, the two raters met to discuss discrepancies in rating regarding one study, which was resolved by discussion. Three studies were randomized controlled trials rated as Level I [32] and Level II [26,33]. Three studies were cohort studies (Level III) with research and concurrent control groups [34][35][36].…”
Section: Study Characteristics and Level Of Evidencementioning
confidence: 99%
See 4 more Smart Citations
“…After independently rating each article using the AACPDM rating scale, the two raters met to discuss discrepancies in rating regarding one study, which was resolved by discussion. Three studies were randomized controlled trials rated as Level I [32] and Level II [26,33]. Three studies were cohort studies (Level III) with research and concurrent control groups [34][35][36].…”
Section: Study Characteristics and Level Of Evidencementioning
confidence: 99%
“…One used a repeated-measures within-subject design [38] and Seven studies were single-subject research and case studies at evidence Level V [7,39,40]. Of the six (35%) studies that used a control group, only Gabriels et al [32] used a control group without horses that mirrored THR intervention methods. Six studies reported using a waitlist control group, and one study [41] employed a design in which each child acted as his or her own control ( Table 2).…”
Section: Study Characteristics and Level Of Evidencementioning
confidence: 99%
See 3 more Smart Citations